PENGARUH PELAKSANAAN TATA TERTIB SISTEM POIN TERHADAP KARAKTER DISIPLIN SISWA SMPN 1 BANTAN KABUPATEN BENGKALIS - Emi Ramdani Emi Ramdani; Sri Erlinda Sri Erlinda; Gimin Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research as a result of their undisciplined students with violating school rules. In this case the school must devise an effective rules against the student discipline code. regulations in education should not contain elements of violence because it can be bad for the development of students. One form of rule that is in use at the school is a point system. According Sceafer (In Yusransyah: 2013) points system is pretty good punishment applied in schools, because this penalty is objective, not using physical violence, enacted as soon as possible and the punishment must be clear and bright. Penalty points also involve the parents so they can help school monitor and awareness to students who commit violations. This study aims to determine whether there Influence Points System Implementation Rules Against Student Disciplinary Character at SMPN 1 Bantan Bengkalis. The population in this study were all students at SMPN 1 Bantan Bengkalis. The sample is determined by using purposive sampling of students who earn as many points as 34 people. Instrument data collection is a questionnaire consisting of 38 questions about the disciplinary character students before and after getting points. Data were analyzed using t-test. hypothesis "There Influence Points System Rules Against Discipline Character SMPN 1 Bantan Bengkalis” acceptable. This is evidenced by a series of t-test to compare the character of discipline for students before and after getting points. From the calculation results obtained t t0 = -8.73 and t table or t = 2.03 = 8.73> 2:03. Due to larger than than t then Ho is rejected.Keywords: Point System Rules, Discipline Characters